Metabolic syndrome: a comprehensive review - C., Ramachandra Bhat; T., Santhosh; K. M., Sudha (International Journal of Basic & Clinical Pharmacology, 2023)
Metabolic syndrome (syndrome X) includes several components like diabetes, hypertension, hyperlipidemia etc. Every patient should undergo detailed assessment for the silent presence of the components of metabolic syndrome. Genetic predisposition, increased nutrient- dense food, decreased physical activity and chronic stress are common in metabolic syndrome. Insulin resistance, obesity and hyperglycaemia are commonly seen which can later lead to serious consequences like cardiovascular complications, thrombotic events etc. Clinical features depend on the components of the metabolic syndrome in a patient. Some may present with complications and advanced disease. For non-diabetic individuals, oral glucose tolerance test is indicated. It is better to study serum uric acid level and to screen for silent kidney stones. Specific drugs are prescribed as indicated. Drugs for stress and insomnia are also prescribed. Thrombotic status of the patient should be considered, and antiplatelet drugs are prescribed if risk factors are present. Non-pharmacological measures like diet modification and increased physical activity should be given on a priority basis. Patient compliance of these two measures should be monitored regularly. Future deployment of “artificial intelligence – powered” predictive diagnostic tests will help in detecting and controlling metabolic syndrome. “At risk” individuals and patients showing some components of metabolic syndrome should undergo full investigations to detect other components of metabolic syndrome. Full range of therapeutic drugs, diet modification and increased physical activity should be prescribed.